Warm Aluminum Foil Blankets to Prevent Hypothermia during Early Breastfeeding after Cesarean Delivery - Sholikhah, Siti Mar’atus; Rubaya, Agus Kharmayana; Meilani, Niken (JURNAL KEBIDANAN, 2024)
Early Initiating Breastfeeding after cesarean delivery can increase the risk of hypothermia in the baby due to the cold temperature of the operating room and the mother's lowered body temperature. To prevent hypothermia, a heating method during breastfeeding initiation is needed. This study aims to evaluate the effectiveness of using aluminum foil warm blankets in preventing hypothermia in newborns after caesarean during early breastfeeding initiation. The study used a True Experiment Pretest Posttest Control Group Design with consecutive sampling. The research groups were randomly allocated. A total of 50 infants were included, with 25 infants receiving aluminum foil warm blankets in the experimental group, and 25 infants receiving warm blankets only in the control group. The treatment was given for 30 minutes in the recovery room, and the infant's temperature was measured with an axillary digital thermometer. Data analysis using the Wilcoxon Signed Rank Test showed that the body temperature of infants increased from moderate hypothermia (35.75°C in the experimental group and 35.8°C in the control one) to mild hypothermia (36.34°C in the experimental group and 36.12°C in the control one). The Mann-Whitney U test showed a significant difference in the average body temperature of newborns between the experimental group and the control group, with a p-value<0.05. The study concluded that using aluminum foil warm blankets is better than using warm blankets alone in increasing the body temperature of babies born through cesarean section during early breastfeeding initiation in the recovery room.